Thermogenesis: Transferrin Receptor 1 Regulates Thermogenic Capacity and Cell Fate in Brown/Beige Adipocytes (Adv. Sci. 12/2020). Issue 12 (24th June 2020) - Li, Jin; Pan, Xiaohan; Pan, Guihua; Song, Zijun; He, Yao; Zhang, Susu; Ye, Xueru; Yang, Xiang; Xie, Enjun; Wang, Xinhui; Mai, Xudong; Yin, Xiangju; et al.
Abstract : In article number 1903366, Fudi Wang, Junxia Min, Liwei Xie, and co‐workers demonstrate the essential role of transferrin receptor 1 (Tfr1) in the thermogenic capacity and cell fate of brown/beige adipocytes. Under cold exposure, Tfr1 expression is transcriptionally regulated by hypoxia‐inducible factor 1α (HIF1α) in beige adipocytes. Targeting Tfr1 serves as a potential strategy for preventing and treating metabolic diseases.